Travellah - The Travel Helper Application - Chan, Yi Fang; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2021)
Traveling is an extraordinary experience every person needs. However, there are a lot of preparations need to be done for a trip. There are many mobile applications can be used to help a person to manage a trip but no application that fully support the trip planning, most of its just consist of part of the functions. To solve this problem an application called Travellah-Travel Helper Application is developed. This application enabling travelers to manage their trip. It combines all of the important functions including schedule of whole trip with a distinct route map synchronize to all the travel buddies, money management and checklist. A sharing platform for travel information by the other traveler’s experience is also provided.  Prototype model is used in the development of this project as this methodology ensures that the end-users interact with the application and provide suggestions that is incorporated into the implementation to create a usable application. This application is developed as Android OS mobile application. We use Java as the language in Android Studio platform assisted by Adobe XD tool to design the user interface.   Testing phase of the application development have shown that the functions of each features are as expected and highly accepted by users.